KEANEKARAGAMAN JENIS ANGGREK ALAM EPIFIT PADA BERBAGAI TUTUPAN TAJUK HUTAN DI DESA BALAI SEBUT KABUPATEN SANGGAU - Sudarso, Dunatus; Astiani, Dwi; Ekamawanti, Hanna Artuti (JURNAL HUTAN LESTARI, 2020)
Epiphytic orchids can be found living naturally in the tropical rainforest. Destruction or degradation of forest area in Balai Sebut District Sanggau Regency due to caused degradation of canopy cover. This condition may affect microclimate which than impacts at the presence of species, one of which is epiphytic orchids that grow naturally in the forest. This study used a survey method with purposive double plot sampling for 1 month (28 Mei – 21 July 2019) in the field. Observation plots were made with a size of 20 x 50 m with a total of 12 plots. The results showed that there where 32 types of epiphytic orchids with a total of 431 individuals. At closed forest canopy cover and had been accomplished (>70%) can be 16 species of orchids with 220 individuals, at forest canopy (50-70%) can be 25 species of orchids with 159 individuals, can be at open forest canopy cover (50%) there were 10 species of orchids with 52 individuals. The dominant orchids species in the three canopy cover Flikingeria bicostata with Celogne peltastes.Keywords: closed forest canopy, epiphytic orchids, medium and open forest canopy, species diversity.